2018
DOI: 10.1007/s12011-018-1353-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Trace Elements and Lipid Peroxidation in Breeding Female Bank Voles Myodes glareolus

Abstract: Recent studies have demonstrated that reproduction reduces oxidative damage in various tissues of small mammal females. The present work was designed to determine whether the reduction of oxidative stress in reproductive bank vole females was associated with changes in tissue trace elements (iron, copper, zinc) that play an essential role in the production of reactive oxygen species. Lipid peroxidation (a marker of oxidative stress) and iron concentration in liver, kidneys, and skeletal muscles of reproducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…For FA(21:0), as one of the important saturated fatty acids (SFA), we speculate that it may affect the incidence of PB by involving the inflammatory process and fetal development like SFA. In addition, we found that various metals in maternal serum had a strong correlation with lipid features. Such relationships had been demonstrated by previous studies, e.g., rare earth elements, essential trace elements, and toxic metals . This suggests that high maternal exposure to various metals may be associated with SPB risk due to their interfering with GP metabolism.…”
Section: Discussionsupporting
confidence: 74%
“…For FA(21:0), as one of the important saturated fatty acids (SFA), we speculate that it may affect the incidence of PB by involving the inflammatory process and fetal development like SFA. In addition, we found that various metals in maternal serum had a strong correlation with lipid features. Such relationships had been demonstrated by previous studies, e.g., rare earth elements, essential trace elements, and toxic metals . This suggests that high maternal exposure to various metals may be associated with SPB risk due to their interfering with GP metabolism.…”
Section: Discussionsupporting
confidence: 74%
“…(Abbreviations: - , data not given; RT , room temperature; GFAAS , graphite furnace atomic absorption spectrometry; ICP-OES , inductively coupled plasma-optical emission spectrometry; ICP-MS , inductively coupled plasma-mass spectrometry; HC , hepatocytes; KC , Kupffer cells; LSEC , liver sinusoidal endothelial cells; HSC , hepatic stellate cells; BMDMs , bone marrow–derived macrophages) Measurement technique Sample type Sample preparation (a) Reagents and treatment (b) Duration (c) Approx. sample amount Analyzed elements Validation by recovery in reference material or by reference method LOD Ref Colorimetric assay Rat Brain cells (astrocytes) (a) Lysis in NaOH for 2 h, then mixing with HCl and iron-releasing reagent (mixture of HCl and KMnO 4 ) for 2 h at 60 °C followed by staining with iron detection reagent (ferrozone, neocuproine, ammonium acetate, ascorbic acid) for 30 min (b) 4.5 h (c) 100 μL of cell lysates Fe Validated by GFAAS as reference method - [ 5 ] Mouse Liver (a) Digestion at 90 °C in HNO 3 and H 2 SO 4 followed by addition of H 2 O 2 (b) Duration not given: Incubation in ferrozine, ascorbic acid, Tris, and HCl at pH = 4 30 min (c) Not given Fe - - [ 4 ] GFAAS Mouse Liver Kidney Gastrocnemius muscle (a) Microwave-assisted digestion in a mixture of HNO 3 and H 2 O 2 ; evaporated to dryness and re-dissolved in water at 200 °C (b) 40 min (c) 250 mg Fe Cu Zn SRM 1577c, bovine liver 95–101% 89–95% 90–95% - [ 9 ] Mouse and human Liver Macrophages (a) Digestion in HNO 3 followed by ultrasonication at 30–40 kHz; if necessary appropriate dilution in water (b) > 30 min (c) Not given Fe - - [ 7 ] ICP-OES SRM Bovine liver (a) M...…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the performance of the proposed method was compared with that of other methods reported recently in literature (see Table 4). Most common practices for iron determination in the field of biomedical research have been and still are colorimetric assays, i.e., photometric detection after adequate staining of the samples (e.g., [4,5]), and/or application of GFAAS (e.g., [5,7,9]). Sensitivity of colorimetric assays is typically much lower than that of atomic spectrometric techniques, allowing detection of Fe in a concentration range between a few micrograms per liter to low milligrams per liter.…”
Section: Analytical Figures Of Merit and Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation